Semantic and metaphysical issues concerning the metascientific debate (P. Melogno & D. Pelegrin [comps.], Realismo, verdad y significado) - Guirado, Matías Alejandro (Analysis. Journal of Philosophical Research, 2018)
A review of the book Realismo, verdad y significado, is made. I bring to the fore the thematic axes of the compilation and make a one-by-one sketchy study of each chapter. The volume broachs the general topic of the justification of scientific knowledge, i.e., tha conditions which decide the epistemological status of a scientific theory or practice. This approach leads the authors to do a bit of metaphysics, that is, to discuss whether and to what extent the posits that guide the researches reliably reveal something about the structure and composition of the world in some of its aspects.